Analisis Butir Soal Ujian Akhir Semester Ganjil Biologi Kelas XI MAN 2 Kota Jambi - Ahmad Subari; Lufri Lufri; Syamsurizal Syamsurizal (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2021)
This study aims to determine the quality of the final exam questions for the odd semester biology class XI MAN 2 Jambi City. The research subjects were 167 students of class XI MAN 2 Jambi City in the 2020/2021 academic year. This research is a descriptive study with data collection techniques through test instruments in the form of multiple choice questions, answer sheets, and answer keys. The data analysis technique used the Anates version 4.0.9 program to determine the reliability, level of difficulty, discriminatory power, distractor quality, and recap of item analysis. The results in this study indicate that the reliability value of the test items is 0.06 with very low criteria. For the item difficulty level, there are 4 questions of